GROW-J: an empirical study of social sustainability, sense of place, and subjective well-being in Jordanian housing development - Ebbini, Genell Wells; Bleibleh, Sahera (Frontiers in Sustainable Cities, 2024)
The country of Jordan is committed to sustainable development goals and public well-being but faces challenges such as high rates of poverty and disaffection, exacerbated by the influx of refugees. This study aimed to evaluate housing-related happiness factors and provide recommendations for integrating these metrics into sustainable housing evaluations. We conducted qualitative interviews and used interpretative phenomenological analysis, grounded in an interpretivist paradigm, to understand Jordanian residents' perspectives on their housing conditions. The research design emphasized capturing the subjective experiences of residents and the meanings they assign to their housing environments. Our findings indicate that social integration and community bonds are crucial for housing happiness, emphasizing cultural continuity, place attachment, social belonging, and dignity. These insights highlight the importance of considering social and psychological outcomes in sustainable housing initiatives, often overshadowed by economic and ecological metrics. We propose recommendations to enhance sustainable housing policies by focusing on social sustainability, contributing to the growing trend of incorporating social and psychological outcomes in green building evaluations. This study offers a framework for future sustainable housing projects to ensure they address the social and psychological needs of residents, thereby improving overall community well-being.